Does asymmetric information cause the home equity bias? - Bravo Ortega, Claudio (Policy research working paper, 2005)
"The home equity bias is one of the many puzzles existing in international finance. This puzzle is characterized by the concentration of domestic equity in any investor's portfolio, which is in contradiction with the benchmark of full diversification in a world mutual fund. Based on Admati's (1985) and Gehrig's (1993) noisy rational expectation models, Bravo-Ortega tries to explain the effect of asymmetric information in the home equity bias puzzle. While asymmetric information helps to explain the puzzle for the case of one domestic and one foreign equity, this result relies on very restrictive assumptions. Using a model with one domestic asset and two foreign assets, the author illustrates that asymmetries of information are also consistent with home equity bias reversals. One proposition generalizes these results. Simulations corroborate the main theoretical predictions of the model presented by the author. This paper is a product of the Office of the Chief Economist, Latin America and the Caribbean Region"--World Bank web site